Comparison of Oncologic Outcomes Between Incomplete Obstructive Colon Cancer and Non-Obstructive Colon Cancer by Tumor Location - Lim, Ji Ha; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Huh, Jung Wook; Park, Yoon Ah; Shin, Jung Kyong (Frontiers in Oncology, 2022)
Introduction Obstruction in colon cancer is a well-known risk factor for worse oncologic outcomes. However, studies on differences in survival of patients with incomplete obstructive colon cancer (IOCC) by tumor location are insufficient. Thus, the aim of this study was to compare oncologic outcomes between IOCC and non-obstructive colon cancer (NOCC) according to tumor location. Methods From January 2010 to December 2015, a total of 2,004 patients diagnosed with stage II or stage III colon adenocarcinoma who underwent elective colectomy were included (IOCC, n = 405; NOCC, n = 1,599). Incomplete obstruction was defined as a state in which colonoscopy could not pass through the cancer lesion but did not require emergent surgery, stent insertion, or stoma formation because the patient was asymptomatic without problem in bowel preparation. Kaplan–Meier method and log-rank tests were used to compare survival between IOCC and NOCC. Multivariable analysis was performed to determine which factors affected survivals. Results Stage III IOCC patients showed significantly lower overall survival (OS) and recurrence-free survival (RFS). Stage II IOCC patients and stage III NOCC patients had similar survival curves. IOCC patients with tumors on the right side showed worse OS than other patients. In multivariable analysis, incomplete obstruction was an independent risk factor for worse OS and RFS in all stages. Tumor located at the right side in stage III was an independent risk factor for RFS (HR: 1.40, p = 0.030). Conclusions Patients with IOCC showed significantly worse survival outcomes than those with NOCC. Stage II IOCC patients and stage III NOCC patients showed similar survival. Patients with stage III IOCC located at the right side showed significantly worse oncologic outcomes than those located at the left side. These results confirm that prognosis is different depending on the presence of incomplete obstruction and the location of the tumor, even in the same stage.